2003
DOI: 10.1099/ijs.0.02700-0
|View full text |Cite
|
Sign up to set email alerts
|

Methanocaldococcus indicus sp. nov., a novel hyperthermophilic methanogen isolated from the Central Indian Ridge

Abstract: An autotrophic, hyperthermophilic methanogen, strain SL43 T , was isolated from a deep-sea hydrothermal chimney sample collected on the Central Indian Ridge at a depth of 2420 m. The coccoid, surface-layer-carrying, Gram-negative-staining cells were heavily flagellated and exhibited a slight tumbling motility. The temperature range for growth at pH 6?5 was 50-86 6C, with optimum growth at 85 6C. The optimum pH for growth was 6?6 and the optimum NaCl concentration for growth was 30 g l "1 . The novel isolate us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Methanocaldococcus spp. are cosmopolitan members of deep‐sea hydrothermal vent communities that typically grow optimally at 80–85°C (Jones et al ., ; Jeanthon et al ., 1998; 1999a,b; L'Haridon et al ., ; Mehta and Baross, ; Ver Eecke et al ., ). Bioenergetic models of growth and maintenance have been made for hydrogenotrophic methanogenesis between −20°C and 130°C (Hoehler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Methanocaldococcus spp. are cosmopolitan members of deep‐sea hydrothermal vent communities that typically grow optimally at 80–85°C (Jones et al ., ; Jeanthon et al ., 1998; 1999a,b; L'Haridon et al ., ; Mehta and Baross, ; Ver Eecke et al ., ). Bioenergetic models of growth and maintenance have been made for hydrogenotrophic methanogenesis between −20°C and 130°C (Hoehler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Immediately after the discovery of the Kairei hydrothermal field, many new genera and species of deep-sea vent chemolithoautotrophs were isolated and described (L'Haridon et al 2003;Moussard et al 2004;Takai et al 2004cTakai et al , d, 2008. A hyperthermophilic hydrogenotrophic methanogen, Methanocaldococcus indicus (L' Haridon et al 2003), and an extremely thermophilic hydrogenotrophic methanogen, Methanotorris formicicus (Takai et al 2004c), identified in the Kairei hydrothermal field represent new species of Methanococcales and important primary producers of chemolithotrophic microbial communities.…”
Section: Microbial Communities and Microorganisms Isolated From The Cmentioning
confidence: 99%
“…Methanocaldococcus jannaschii DSM 2661 T (Jones et al, 1983), Methanotorris igneus DSM 5666 T (Burggraf et al, 1990) and Methanothermococcus thermolithotrophicus DSM 2095 T (Huber et al, 1982) were available from our in-house culture collection. Methanocaldococcus fervens DSM 4213 T (Jeanthon et al, 1999), Methanocaldococcus indicus DSM 15027 T (L'Haridon et al, 2003), Methanocaldococcus infernus DSM 11812 T (Jeanthon et al, 1998) and Methanocaldococcus vulcanius DSM 12094 T (Jeanthon et al, 1999) were obtained from the Deutsche Sammlung von Mikroorganismen und Zellkulturen (Braunschweig, Germany). For comparative studies, all strains were grown in MJ medium.…”
Section: Analysis Of the Gold Grids Revealed That Cells Of Strain Kinmentioning
confidence: 99%
“…All strains of the genus Methanocaldococcus described so far have been isolated from deep submarine habitats, e.g. hydrothermally heated material (Zhao et al, 1988) or chimney samples (Jones et al, 1983;Jeanthon et al, 1998Jeanthon et al, , 1999L'Haridon et al, 2003), whereas the genus Methanotorris was originally described from a shallow submarine hydrothermal vent (Burggraf et al, 1990). In general, their requirement for selenium and the high motility of cells allow differentiation of the genus Methanocaldococcus from Methanotorris (Whitman et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation